2017
DOI: 10.1111/jorc.12206
|View full text |Cite
|
Sign up to set email alerts
|

Could intradialytic nutrition improve refractory anaemia in patients undergoing haemodialysis?

Abstract: IDPN has a good role in improving refractory anaemia by significantly increasing haemoglobin levels, body weight, and serum albumin levels. The intervention also significantly decreases the MIS of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…2 ). In agreement with the current study but having lower number of participants, certain earlier randomized trials 19 , 24 showed that serum albumin significantly increased after receiving IDPN when compared with the control arm without IDPN. Previous experimental studies by Pupim and co-workers 25 , 26 also supported these observations by illustrating that nutritional support in the form of IDPN enhanced the fractional synthetic rate of albumin in the liver determined by primed constant stable isotope labeled amino acid infusion and increased whole-body protein synthesis.…”
Section: Discussionsupporting
confidence: 92%
“…2 ). In agreement with the current study but having lower number of participants, certain earlier randomized trials 19 , 24 showed that serum albumin significantly increased after receiving IDPN when compared with the control arm without IDPN. Previous experimental studies by Pupim and co-workers 25 , 26 also supported these observations by illustrating that nutritional support in the form of IDPN enhanced the fractional synthetic rate of albumin in the liver determined by primed constant stable isotope labeled amino acid infusion and increased whole-body protein synthesis.…”
Section: Discussionsupporting
confidence: 92%
“…IDPN is not to be intended as a long‐lasting therapy; in fact, ONS should be restarted and IDPN should be discontinued as soon as possible based on the combination of three of the following criteria: stable serum albumin >3.8 mg/dL for 3 months; improvement in subjective global assessment (SGA) score to A (well‐nourished) or B (moderately malnourished); clinical examination of improved nutritional status; increase in protein and energy oral intake to >1.0 g/kg/d and to >30 kcal/kg/d . Despite the lack of studies demonstrating any benefit of IDPN on mortality, there is convincing evidence about its positive effects on nitrogen balance, anthropometric parameters and serum prealbumin, a surrogate parameter for hard outcomes in malnourished hemodialysis patients . Such early benefits of IDPN can be identified as soon as after 1 month of treatment when prealbumin is monitored .…”
Section: Nutritional Needs In Esrd Patientsmentioning
confidence: 99%
“…Such early benefits of IDPN can be identified as soon as after 1 month of treatment when prealbumin is monitored . A recent but small, randomized, controlled trial designed to evaluate the efficacy of IDPN therapy in malnourished patients with refractory anemia suggested an improvement in nutritional status assessed by the malnutrition inflammation score (MIS), BMI and albumin, as well as an improvement in refractory anemia . Despite its possible risks that must be take into consideration (Figure ), IDPN seems to be metabolically safe …”
Section: Nutritional Needs In Esrd Patientsmentioning
confidence: 99%
“…Anaemia is also an issue for patients with CKD and is one of the factors which impinges significantly on quality of life and cardiovascular complications. Managing iron status during dialysis has been shown to reduce inflammation, which will improve other clinical outcomes .…”
Section: Nutritional Status and Clinical Outcomesmentioning
confidence: 99%